PENGARUH CUSTOMER SATISFACTION TERHADAP REVISIT INTENTION DIMEDIASI OLEH WORD OF MOUTH DI RESTORAN X DI KOTA BANDUNG - Siti Fatimah; Fransisca Mulyono (Politeknik Bisnis Indonesia, 2024)
This research was conducted at Restaurant X in Bandung with the interest of researchers to see the phenomenon of Restaurant X which was able to open 2 branches, namely Buahbatu and Dago during the COVID-19 pandemic. The purpose of this study is to determine the influence of customer satisfaction directly on revisit intention and the factors that most influence word of mouth as a mediating variable on revisit intention at Restaurant X in the city of Bandung. This type of research is explanatory research. Data was collected by distributing questionnaires to consumers at Restaurant X. The proposed model was modeled using PLS-SEM with a sample of 342 respondents. The findings of this study are, customer satisfaction does not have a direct influence on revisit intention. Customer satisfaction has a direct influence on word of mouth and word of mouth has a direct influence on revisit intention. Word of mouth mediates between customer satisfaction and revisit intention. Restaurant X in the city of Bandung needs to focus on increasing customer satisfaction both in terms of service and product quality because this variable is the main factor for customers to revsit and can increase revenue for the company.